The Development of Interactive Learning Media to Improve Students' Motivation on Trigonometry - Saepuloh Saepuloh; Rudi Priyadi; Nani Ratnaningsih (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2022)
The problem found by the researchers was the lack of student motivation in learning mathematics. Teachers must try to create innovations to make learning fun, that is, through learning media. Learning media that can create motivation and student activity is interactive learning media in the form of multimedia with Articulate Storyline. This study aimed to develop and analyze the effectiveness of using interactive learning media developed using Articulate Storyline in the learning motivation view. This research includes development research with a 4D model from Thiagarajan. It consists of define, design, develop, and dissemination stages. The study was conducted at MA Assa’adah Jamanis Tasikmalaya. Data collection techniques are observation, interviews, questionnaires, and tests. Data analysis techniques are validity, practicality, and effectiveness analysis. The study results stated that the learning media was feasible based on the validation of material experts and media experts and student responses. Learning motivation increased seen from before and after using interactive media created using Articulate Storyline. There is also an increase in student learning outcomes based on the average pre-test and post-test results. The use of these learning media can increase students' learning motivation to participate in learning. Interactive media are recommended as a learning resource or learning media that can be combined with varied learning models/methods.